FATTY ACID COMPOSITION INDUCED SOMATIC EMBRYO OF Jatropha curcas IN BIOREACTOR - Ismidianty, Devi
Jatropha curcas is one of the potential plant to be developed as biodiesel, but there are constrains to meet the demand for large-scale production. Therefore, alternative method should be developed, such as by tissue culture, which has been widely used for the production of secondary metabolite. Somatic embryo culture has been known to accumulate food reserve such as fat, and has the ability to continue to grow, so it could be adventageous to be applied on a large scale by using a bioreactor. However, its productivity is limited by the availability of oxygen. Therefore the aim of this study was to obtain mature somatic embryo of J. curcas, to obtain optimum air-flow rate that induce fatty acids composition that suitable for biodiesel from somatic embryo culture of J. curcas in air-lift bioreactor, to analize fatty acids composition of J. curcas somatic embryo that cultured in air-lift bioreactor with various air-flow rate. Hypocotyl explant, were planted on MS solid embryogenic callus induction medium containing vitamin B5 with the addition of 1.35×10-5 M 2,4-D; 4.4×10-6 M kinetin and 30 g/L sucrose (DK5) for four weeks. Four-week-old friable callus was then transferred into the liquid MS medium for embyogenic cell suspension initiation with the addition of vitamin B5; 6.75×10-6 M 2,4-D; 4.4×10-7 M kinetin and 20 g/L sucrose (MJ2). They were cultured for one week under 16 hours fotoperiodism condition. In the MJ2medium, callus produced pre-embryogenic aggregates (PEM), which were cultured for two weeks and subcultured every week until embyogenic cell suspension was obtained, indicated as globular embryos with a rounded smooth surface compact structure. In the next stage, the suspension was transferred into a pretreatment (PT) medium i.e. liquid MS medium with the addition of vitamin B5 without KNO3, 6 g/L K-citrate monohydrate; 1.35×10-5 M 2,4-D; 4.4×10-7 M kinetin dan 20 g/L sucrose and cultured for two weeks without subculture. At this stage, more globular structures were formed and embryos that develop into heart stage started to form. Culture was then transferred into the embryo maturation medium with ½ MS macro element composition, with the addition 10 mg/L ascorbic acid, 50 mg/L citric acid, 25 mg/L adenine sulphate, 100 mg/L glutamine, 0.5 ppm IAA, 0.3 ppm GA3 and 20 g/L sucrose (IG2). Cultures produced more globular-stage and heart-stage-embryo at this stage. After that, 10 g of embryos was tranfered into a 500 ml IG2 medium with the addition of 10 % (w/v) PEG 4000, and cultured in a bioreactor with variations i.e. 0.2, 0.4 and 0.6 L/min air flow rate treatment in 16 hours photoperiodism conditions for 10 days. The extract was analysed for total lipid content using modified method by Zou et al (1995), followed by fatty acid analysis by GCMS. The result showed that air flow rate of 0,2 L/min gave highest growth (7,85 g) and total lipid extract (63,6